Pseudo-Hyperaldosteronism Arising from Licorice Cough Syrup Self-Ingestion: A Case Report - Chien-Chun Liao; Kun-Te Lin (Reports)
Background and Clinical Significance: Licorice (glycyrrhiza glabra) cough syrup intoxication is manifested with refractory hypokalemia, hypertension, and metabolic alkalosis. The transformation of glycyrrhiza glabra metabolic into glycyrrhetic acid after ingestion further inhibits the 11-β-hydroxysteroid dehydrogenase-2 enzyme, impeding the conversion of cortisol into cortisone. The accumulation of cortisol can also stimulate mineralocorticoid receptors, which leads to a pseudo-hyperaldosteronism-like effect. Case Presentation: We report a 60-year-old male patient with licorice intoxication due to the chronic consumption of licorice cough syrup. He exhibited a transient seizure lasting approximately one minute. Initially, hypokalemia (potassium level was 2.0 mmol/L), metabolic alkalosis, and QT interval prolongation with premature ventricular complexes were demonstrated on his electrocardiogram. Despite the administration of both intravenous and oral potassium supplements over two days, there was no significant improvement in hypokalemia. Spironolactone, an aldosterone receptor antagonist, was administered in addition to ongoing potassium supplementation from the 3rd day. This intervention led to a rapid normalization of hypokalemia in one day. The patient was ultimately discharged on the 6th day without any subsequent complications. Conclusions: The licorice-induced chronic intoxication, which led to pseudo-hyperaldosteronism and refractory hypokalemia, was successfully managed with aggressive potassium supplementation and spironolactone treatment.